Treating Skin and Soft Tissues Infections in a University Hospital - Araújo, Margarida; Mosca, Ana Margarida; Carvalho, Alexandre; Alves, Joana (Gazeta Médica, 2022)
INTRODUCTION: Incidence of skin and soft tissue infections (SSTIs) is increasing worldwide. These infections represent an important reason for hospital admission. Proper management of these patients is of paramount importance, regarding prognosis and healthcare-associated costs. METHODS AND RESULTS: A retrospective observational study was developed to evaluate clinical practice, risk factors for SSTIs and outcomes in patients with SSTIs. Study population comprised patients hospitalized with SSTIs. A total of 267 SSTIs were identified. Microbiological isolate was obtained in most of necrotizing infections and surgical wounds. Gram-positive organisms were the most frequent agents. In necrotizing infections, 70% of the isolates were polymicrobial. First-line antibiotics for initial management of skin superficial infections were penicillins. However, almost 1/3 of erysipelas and cellulitis were treated with broad-spectrum antibiotics. In necrotizing infections, penicillins (broad-spectrum penicillins) also prevailed, mostly in combination antimicrobial regimens. Vancomycin was used in 55.6% of cases of surgical wounds. Mean antibiotic therapy duration ranged from 9-19 days, with longer periods in deeper infections. A high percentage of antibiotic switch (66.7%) occurred in patients with necrotizing infections. Mean time to surgical intervention was 40.8 hours. Overall mortality rate was 9.7%. CONCLUSION: The diagnosis of SSTIs is clinical. Clinical approach to initial choice of antimicrobial therapy is based on multiple factors related to the patient, the bacteria, and the drug. A multidisciplinary team is essential to improve the quality of patient care.